The effects of maltodextrin as a drying aid and drying temperature on production of tamarind powder and consumer acceptance of the powder - Ekpong, A. (2018)
Tamarind pulp with varying levels of added maltodextrin was foam-mat dried to improve the stability of the tamarind and to study consumer acceptance and attitudes towards the tamarind powder. Tamarind foam-mats were prepared using hydroxypropyl methycellulose (HPMC) as a foaming agent and maltodextrin at either 0%, 5%, 10%, or 15% as a drying aid. The resulting mixtures were foamed and dried at either 55OC, 60OC, or 70OC. Increasing the maltodextrin content resulted in a lighter colour, with a decrease in redness and yellowness. Also the pH increased and the total acidity decreased with increasing maltodextrin. Dispersibility of the tamarind powder was improved by adding maltodextrin. A consumer test (n = 114) found increasing the amount of added maltodextrin also improved the overall acceptance score. The sample with 15% maltodextrin added, then dried at 70OC had the highest overall acceptance score. Investigation into the buying behaviour of the consumers found participants would consider purchasing the tamarind powder if the price range was USD 0.16-0.19 per 10 g (c.a. 5-6 Baht). Moreover, the product being approved by the Food Standard Institute was the most important variable affecting buying decisions, with secondary considerations being product characteristics such as colour, odour and taste. The consumers suggested that the tamarind powder could replace tamarind pulp for cooking; be used as an instant juice powder; added to Thai curry paste, or; used as an ingredient in cosmetics.